Controlling the defect density to improve the output power of InGaN/GaN-based vertical light-emitting diodes by using substrates patterned with SiO2 lenses. Issue 27 (21st September 2016) - Kang, Daesung; Kim, Da-Som; Kim, Sun-Kyung; Song, Kiyoung; Jung, Myunghoon; Jeong, Hwanhee; Song, June-O; Seong, Tae-Yeon
Abstract: In this study, we investigated the effect of SiO2 lenses on the output power of InGaN/GaN-based vertical light-emitting diodes (VLEDs; wavelength = 445 nm) and compared the results to those of reference VLEDs without the SiO2 lenses (planar samples). Arrays of SiO2 lenses (pitch = 3 μm, width = 2.5 μm, height = 1.0 μm) were formed on c-plane sapphire substrates. The external quantum efficiency (EQE) of the packaged VLEDs with planar and patterned substrates was characterised. At 5 mA, the EQE of the patterned samples was 150% higher than that of the planar samples. A patterned, N-polar, n -GaN sample contained far fewer nanopipes (approximately 2.2 × 10 5 cm −2 ) than a planar n -GaN sample (approximately 2.4 × 10 6 cm −2 ). Furthermore, the patterned samples contained far fewer threading dislocations (approximately 1.0 × 10 8 cm −2 ) than the planar samples (approximately 5.0 × 10 8 cm −2 ). Scanning electron microscopy (SEM) images showed that the photoelectrochemical (PEC)-etched patterned samples contained cones that were 150% larger than that of the PEC-etched planar samples. In addition, SEM images, cathode luminescence measurements and finite-difference time-domain simulations were used to characterise the improved light output of the patterned samples.